Fast response photogating in monolayer MoS2 phototransistors. Issue 38 (20th September 2021) - Vaquero, Daniel; Clericò, Vito; Salvador-Sánchez, Juan; Díaz, Elena; Domínguez-Adame, Francisco; Chico, Leonor; Meziani, Yahya M.; Diez, Enrique; Quereda, Jorge
Abstract : We identify a rapidly-responding mechanism for photogating in monolayer MoS2 phototransistors that becomes the dominant contribution to photoresponse under high-frequency light modulation. Abstract : Two-dimensional transition metal dichalcogenide (TMD) phototransistors have been the object of intensive research during the last years due to their potential for photodetection. Photoresponse in these devices is typically caused by a combination of two physical mechanisms: the photoconductive effect (PCE) and photogating effect (PGE). In earlier literature for monolayer (1L) MoS2 phototransistors, PGE is generally attributed to charge trapping by polar molecules adsorbed to the semiconductor channel, giving rise to a very slow photoresponse. Thus, the photoresponse of 1L-MoS2 phototransistors at high-frequency light modulation is assigned to PCE alone. Here we investigate the photoresponse of a fully h-BN encapsulated monolayer (1L) MoS2 phototransistor. In contrast with previous understanding, we identify a rapidly-responding PGE mechanism that becomes the dominant contribution to photoresponse under high-frequency light modulation. Using a Hornbeck–Haynes model for the photocarrier dynamics, we fit the illumination power dependence of this PGE and estimate the energy level of the involved traps. The resulting energies are compatible with shallow traps in MoS2 caused by the presence of sulfur vacancies.